2022
DOI: 10.1108/jhtt-02-2021-0039
|View full text |Cite
|
Sign up to set email alerts
|

Passive Wi-Fi visitor analytics and food truck engagement: a feasibility study

Abstract: Purpose This paper aims to test whether passive Wi-Fi visitor analytics is a useful and effective method to measure consumer engagement towards food trucks located within an outdoor activation area at an Australian metropolitan university. Design/methodology/approach Using passive Wi-Fi visitor analytics to ping and track smart devices, data was collected over 90 weekdays capturing data from 522,548 unique smart devices. Findings The data collected in this feasibility study was able to identify the most an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Because tourist mobility plays a critical role in aspects of destination marketing, several studies on tourist mobility have been conducted in the context of tourism management and sustainable development (McKercher and Lau, 2008; Stienmetz et al , 2021; Park et al , 2021) have proposed identifying similarities in tourist mobility among individual travelers from spatial and temporal perspectives. In other work, Nyns and Schmitz (2022) have analyzed tourists’ overnight stays with reference to official statistics, while Sung et al (2022) have shown what customer engagement with food trucks implies for marketing. Both of those studies indicated that understanding tourist mobility is essential from the perspective of destination management.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Because tourist mobility plays a critical role in aspects of destination marketing, several studies on tourist mobility have been conducted in the context of tourism management and sustainable development (McKercher and Lau, 2008; Stienmetz et al , 2021; Park et al , 2021) have proposed identifying similarities in tourist mobility among individual travelers from spatial and temporal perspectives. In other work, Nyns and Schmitz (2022) have analyzed tourists’ overnight stays with reference to official statistics, while Sung et al (2022) have shown what customer engagement with food trucks implies for marketing. Both of those studies indicated that understanding tourist mobility is essential from the perspective of destination management.…”
Section: Literature Reviewmentioning
confidence: 99%
“…New digital technologies such as smartphones now provide a new source for alternative data, namely, smartphone data [e.g. global positioning system (GPS) coordinates and Wi-Fi; Sung et al , 2022] and social media data (e.g. geotagged information; Kim and Chae, 2018; Kim et al , 2021; Xu et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%